Analisis Persoalan dan Solusi Keberlanjutan UKM: Studi Kasus pada Usaha Karyawan PHK di Kota Balikpapan - Hasto Finanto; Dessy Handasary; Totok Ismawanto; Saiful Ghozi (ISAS (Indonesian Society of Applied Science), 2021)
This article provides an analysis of the situation and the need for solutions to businesses founded by employees who were affected by the layoffs. The business that was established was a new business that was categorized as Small and Medium Enterprises (SME). The business established by this partner has so far not been going well because it has not generated a stable cash flow. Even SME partners stated that they are still losing money. Many products that are marketed experience a return because the sales system is still in the stalls / shops and does not sell well. The proposed solution is divided into several things, namely management, capital access, marketing, distribution and production technology